2020
DOI: 10.1016/j.cjph.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic monopoles from a hidden magnetic symmetry

Abstract: It is proposed that Magnetic Monopoles (MMs) could originate from a new U(1) M symmetry. Such an abelian symmetry is then assumed to be related to the conservation of a magnetic number M. This magnetic number is associated with massive MMs from an expected high scale breaking of this magnetic symmetry. The involved scales are approached and the properties of such MMs are investigated along with the prospects for their detection. 114.80.Hv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…In particular, it has been shown that the single electric and magnetic charges in ten dimensions could be viewed from the 4-dimensional non-compact spacetime standpoint as dyonic charges, being particles carrying simultaneous existence of the electric and the magnetic charges [6]. A dyon with a zero electric charge is usually referred to as a magnetic monopole [7,8]. These objects are hypothetical particles predicted in many extended models and grand unified theories [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that the single electric and magnetic charges in ten dimensions could be viewed from the 4-dimensional non-compact spacetime standpoint as dyonic charges, being particles carrying simultaneous existence of the electric and the magnetic charges [6]. A dyon with a zero electric charge is usually referred to as a magnetic monopole [7,8]. These objects are hypothetical particles predicted in many extended models and grand unified theories [9,10].…”
Section: Introductionmentioning
confidence: 99%